God, guns, and sedition: far-right terrorism in America - Hoffman, Bruce (A Council on Foreign Relations book, 2024)
"Shocking acts of terrorism have erupted from violent American far-right extremists in recent years, including the 2015 mass murder at a historic Black church in Charleston and the January 6, 2021, attack on the U.S. Capitol. These incidents, however, are neither new nor unprecedented. They are the latest flashpoints in a process that has been unfolding for decades, in which vast conspiracy theories and radical ideologies such as white supremacism, racism, antisemitism, xenophobia, and hostility to government converge into a deadly threat to democracy. God, Guns, and Sedition is the definitive account of the rise of far-right terrorism in the United States-and how to counter it. Leading experts Bruce Hoffman and Jacob Ware trace the historical trajectory and assess the present-day dangers of this violent extremist movement. They combine authoritative, nuanced analysis with gripping storytelling and portraits of the key leaders of the American far right and their followers. Hoffman and Ware highlight developments including the use of cutting-edge communications technology; the embrace of leaderless resistance or lone wolf strategies; the emergence of characteristic tactics and targets; infiltration and recruitment in the military and law enforcement; and the far right's intricate relationship with mainstream politics. An unparalleled examination of one of today's great perils, God, Guns, and Sedition offers practical recommendations to halt the growth of the far right and address the terrorist threat"--